Loss prevention for hog farmers: Insurance, on-farm biosecurity practices, and vaccination - Zhang, Yue-hua; Li, Chu-Shiu; Liu, Chwen-Chi; Chen, Kevin Z. (International Food Policy Research Institute, 2011)
Using agricultural household survey data and claim records from insurers for the year 2009, this paper analyzes hog producers' choice of means of loss prevention and identifies the relationships among biosecurity practices, vaccination, and hog insurance. By combining one probit and two structural equations, we adopt three-stage estimations on a mixed-process model to obtain the results.The findings indicate that biosecurity practices provide the basic infrastructure for operating pig farms and complement both the usage of quality vaccines and the uptake of hog insurance. In addition, there is a strong relationship of substitution between quality of vaccine and demand for hog insurance. Hog farmers that implement better biosecurity practices are more likely to seek high-quality vaccines or buy into hog insurance schemes but not both. For those households with hog insurance, better biosecurity status, better management practices, and higher-quality vaccine significantly help to reduce loss ratios. However, we also find a moral hazard effect in that higher premium expenditure by the insured households might induce larger loss ratios.